Antibacterial Properties of Nano-particles in Dental Restorative Materials: Literature Review - Aljubour, Isra; Aljubour, Ala (International Journal of Innovative Research in Medical Science, 2020)
Nanotechnology has been receiving a great importance because of its ability to modulate materials into their nano size. This has drastically led to many changes in chemical, physical and optical properties of almost all metals. The aim of the present literature review is to examine and quantitatively analyze the current evidence for the addition of different nanoparticles into dental restorative materials, to determine whether their incorporation increases the antibacterial/antimicrobial properties of the materials. The incorporation of nanoparticles into dental restorative materials was a favorable option we found during our review; the antibacterial activity of nanoparticle-modified dental materials was significantly higher compared with the original unmodified materials, TiO2 nanoparticles providing the greatest benefits. However, the high heterogeneity among the articles reviewed points to the need for further research and the application of standardized research protocols.